2022
DOI: 10.3390/land12010094
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off between Land Use Pattern and Technical Efficiency Performance: Evidence from Arable Crop Farming in Tunisia

Abstract: Cereal, oilseed, and protein (COP) production is an important sector contributing to Sustainable Development Goals (SDGs) in Tunisia. COP farms often diversify their production patterns to stabilize their income sources and spread production risk across crops. However, crop diversity may entail an inefficient use and management of resources to achieve the desired output. In addition, the COP sector still shows a low productivity level, depending on weather conditions in Tunisia. In this context, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(98 reference statements)
1
1
0
Order By: Relevance
“…Comparison with previous studies using SFA framework allows to check the confidence and robustness of our results if they concur or not with other findings obtained from other estimation methods and whether they fall in the range of existing efficiency estimates (Balcombe et al, 2006;Guesmi et al, 2015). We found relatively close efficiency performance with some differences due to the application of different estimation methods, databases (countries and time) and hypotheses (Baráth et al, 2021;Guesmi et al, 2023). Manevska-Tasevska et al (2017) used the parametric stochastic frontier random effects that reported close averages TE of 80% among Swedish farms.…”
Section: Em Pi R Ica L R E Su Ltssupporting
confidence: 83%
“…Comparison with previous studies using SFA framework allows to check the confidence and robustness of our results if they concur or not with other findings obtained from other estimation methods and whether they fall in the range of existing efficiency estimates (Balcombe et al, 2006;Guesmi et al, 2015). We found relatively close efficiency performance with some differences due to the application of different estimation methods, databases (countries and time) and hypotheses (Baráth et al, 2021;Guesmi et al, 2023). Manevska-Tasevska et al (2017) used the parametric stochastic frontier random effects that reported close averages TE of 80% among Swedish farms.…”
Section: Em Pi R Ica L R E Su Ltssupporting
confidence: 83%
“…As LUE usually comprises several indicators, it needs to be downscaled to a single indicator. A number of methods have been used in the existing literature to achieve this, e.g., the stochastic frontier production function model [45], locational entropy [46], data envelopment analysis (DEA) [47], the super efficiency slack-based measure (SBM) model [48], and the entropy method [16]. All of these methods are excellent, and researchers choose them mainly according to the characteristics and needs of the study.…”
Section: Methods For Downscaling the Indicators: Entropy Methodsmentioning
confidence: 99%